2021
DOI: 10.4149/neo_2020_200202n101
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts promote cell proliferation and invasion via paracrine Wnt/IL1β signaling pathway in human bladder cancer

Abstract: Bladder cancer (BC) is the most common urinary system malignancy worldwide. However, the molecular mechanisms underlying its progression remain largely unexplo red. Accumulating evidence indicates that the cancer-associated fibroblasts (CAFs), major constituents of tumor stroma, play a key role in tumor development. Herein, we have successfully isolated CAFs and paired normal fibroblasts (NFs) from bladder cancer tissues. We observed that the conditional medium from bladder cancer (CM-CAF) could significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…For the control cells, the increase ranges from 16% (for the 1:10 ratio) to 35% (for the 1:5 ratio), for the cells dosed with GNPs it ranges from 20% (for the 1:10) to 33% (for the 1:5), for the irradiated cells it ranges from 8% (for the 1:10) to 23% (for the 1:5), and for the irradiated/GNP dosed cells it ranges from 6% (for the 1:10) to 20% (for the 1:5). The reason behind that is that CAFs not only encourage radioresistance but also promote cancer cell growth through paracrine signals [ 55 , 66 , 67 , 68 , 69 ]. Interestingly, Yang et al found a substantial decrease in cell proliferation of natural killer cells when co-cultured with irradiated or non-irradiated CAFs vs. when co-cultured with normal fibroblasts [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the control cells, the increase ranges from 16% (for the 1:10 ratio) to 35% (for the 1:5 ratio), for the cells dosed with GNPs it ranges from 20% (for the 1:10) to 33% (for the 1:5), for the irradiated cells it ranges from 8% (for the 1:10) to 23% (for the 1:5), and for the irradiated/GNP dosed cells it ranges from 6% (for the 1:10) to 20% (for the 1:5). The reason behind that is that CAFs not only encourage radioresistance but also promote cancer cell growth through paracrine signals [ 55 , 66 , 67 , 68 , 69 ]. Interestingly, Yang et al found a substantial decrease in cell proliferation of natural killer cells when co-cultured with irradiated or non-irradiated CAFs vs. when co-cultured with normal fibroblasts [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our Tg-Twist1 iEC+ mice, overactivation of Wnt/β-catenin signaling by Ctnna1 mutation can lead to defective retinal angiogenesis, including slower vascular progression, increased EC proliferation, and greater pathological NV ( Zhu et al, 2021 ). Overactivation of Wnt/β-catenin signaling can promote cell proliferation and is well established in multiple cell types ( Li et al, 2020 ; Yang et al, 2021 ). Why did the progression of retinal vasculature from the optic nerve to the peripheral retina seem slowed under the condition of TWIST1 promotes EC proliferation?…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase reverse transcriptase has become an important target for the diagnosis and treatment of human tumours [ 38 , 39 ]. Activation of the hTERT gene is strictly regulated by a variety of signalling pathways in different human tumours, specifically the Wnt/β-catenin, NF-κB and c-Myc signalling pathways [ 10 , 13 , 28 , 40 , 41 ]. However, during ALV-J-induced tumorigenesis, the molecular mechanism by which the chTERT gene regulates the Wnt/β-catenin signalling pathway and participates in cell growth and virus replication is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this pathway is exemplified by evidence that both the overexpression and underexpression of target genes involved in this pathway result in various diseases. Appropriate regulation of the Wnt/β-catenin signalling pathway is key for cells to carry out their normal functions [ 28 , 30 ]. The Wnt/β-catenin signalling pathway has been implicated in the transcriptional reactivation of hTERT in cancer cells; transient activation of Wnt/β-catenin induces hTERT mRNA expression and elevates telomerase activity in different cell lines [ 12 , 31 33 ].…”
Section: Introductionmentioning
confidence: 99%